2015
DOI: 10.1155/2015/352012
|View full text |Cite
|
Sign up to set email alerts
|

A Low Computational Complexity SML Estimation Algorithm of DOA for Wireless Sensor Networks

Abstract: We address the problem of DOA estimation in positioning of nodes in wireless sensor networks. The Stochastic Maximum Likelihood (SML) algorithm is adopted in this paper. The SML algorithm is well-known for its high resolution of DOA estimation. However, its computational complexity is very high because multidimensional nonlinear optimization problem is usually involved. To reduce the computational complexity of SML estimation, we do the following work. (1) We point out the problems of conventional SML criterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…According to [9,22], the SML criteria is derived based on the following assumptions. (A1)

The array configuration is known and any p steering vectors for different q directions are linearly independent, i.e., the matrix bold-italicAfalse(Θfalse) has full rank.

(A2)

bold-italicnfalse(tifalse) are statistically independent samples from a complex Gaussian random vector with zero mean and the covariance matrix σ2Ip, where bold-italicIp is a p×p identity matrix and σ2 is an unknown real number.

(A3)

bold-italicsfalse(tifalse) are independent samples from a complex Gaussian random vector which has zero mean and signal covariance matrix S and is independent of the noise (bold-italicsfalse(tifalse) are independent of bold-italicnfalse(tjfalse) for any i and j ).

…”
Section: System Model and Problem Formulationsmentioning
confidence: 99%
“…According to [9,22], the SML criteria is derived based on the following assumptions. (A1)

The array configuration is known and any p steering vectors for different q directions are linearly independent, i.e., the matrix bold-italicAfalse(Θfalse) has full rank.

(A2)

bold-italicnfalse(tifalse) are statistically independent samples from a complex Gaussian random vector with zero mean and the covariance matrix σ2Ip, where bold-italicIp is a p×p identity matrix and σ2 is an unknown real number.

(A3)

bold-italicsfalse(tifalse) are independent samples from a complex Gaussian random vector which has zero mean and signal covariance matrix S and is independent of the noise (bold-italicsfalse(tifalse) are independent of bold-italicnfalse(tjfalse) for any i and j ).

…”
Section: System Model and Problem Formulationsmentioning
confidence: 99%
“…Among these algorithms, it is well known that ML and WSF have the highest accuracy of DOA estimation [13][14][15]. However, it is also well demonstrated that the computational complexity of them is also the highest because the criteria of them are nonlinear multi-dimensional optimization [13][14][15][16]. e second step is how to get the DOAs from the criteria, i.e., the estimation process.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, this kind of algorithm needs a large number of training samples. e second type is heuristic algorithms for simulating biological behaviors in nature such as Genetic Algorithm (GA) [20], Ant Colony Algorithm [21], and Particle Swarm Optimization (PSO) algorithm [16,22,23]. ese algorithms are all population-based iterative techniques.…”
Section: Introductionmentioning
confidence: 99%